Rancang Bangun Sistem Penangkap Citra Berdaya Rendah dengan Supply Power Panel Surya - Muhammad Daffa Firmansyah; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Technological developments continue to grow, especially in the world of information technology. Internet of Things (IoT) is one result of technological developments. One tool that uses IoT concept is IoT camera. Before there was an IoT camera system, there was also a conventional system called Closed Circuit Television (CCTV). CCTV is often installed to monitor residential and urban areas. However, the use of CCTV electricity is high because it has to record for 24 hours. With this weakness, this research proposes an image capture tool that implements the Event Triggered method and Processor State Control to reduce power usage and use Energy Harvesting to utilize natural energy sources as the main energy source. This study obtained an average duration of battery life of 33 hours 1 minute 20 seconds and estimated battery life when system is active is 9.33 hours and 140 hours when system is in sleep. Taverage increase in battery charge is 85.45% of the nominal battery voltage. The average accuracy of PIR sensor is 60% and the average electric current when motion is detected is 0.23mA and when no movement is detected is 0.09mA. The decrease in electric current for the ESP32-CAM is -92.88% and for the SIM7600C1 is -86.95%. The average circuit power used is 0.74 watts. The accuracy of uploading image is 100% with an average upload duration of 1 minute 28.7 seconds.